2014
DOI: 10.1128/jb.01270-13
|View full text |Cite
|
Sign up to set email alerts
|

Essentiality of DevR/DosR Interaction with SigA for the Dormancy Survival Program in Mycobacterium tuberculosis

Abstract: The DevR/DosR regulator is believed to play a key role in dormancy adaptation mechanisms of Mycobacterium tuberculosis in response to a multitude of gaseous stresses, including hypoxia, which prevails within granulomas. DevR activates transcription by binding to target promoters containing a minimum of two binding sites. The proximal site overlaps with the SigA ؊35 element, suggesting that DevR-SigA interaction is required for activating transcription. We evaluated the roles of 14 charged residues of DevR in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 38 publications
2
57
0
Order By: Relevance
“…DosS acts as a redox sensor and DosT as a hypoxia sensor, illustrating the integration and differentiation of M. tuberculosis stress responses (105). Genetic disruption of the dosRST TCS results in reduced bacterial survival under low-oxygen conditions, in mouse models that develop hypoxic lesions, and in a nonhuman primate macaque model of infection (106)(107)(108)(109).…”
Section: Nonessential Tcss and Tfs: Special Forces Of The Stress Respmentioning
confidence: 99%
“…DosS acts as a redox sensor and DosT as a hypoxia sensor, illustrating the integration and differentiation of M. tuberculosis stress responses (105). Genetic disruption of the dosRST TCS results in reduced bacterial survival under low-oxygen conditions, in mouse models that develop hypoxic lesions, and in a nonhuman primate macaque model of infection (106)(107)(108)(109).…”
Section: Nonessential Tcss and Tfs: Special Forces Of The Stress Respmentioning
confidence: 99%
“…To demonstrate a high level of hypoxia, Mtb wild-type mice and mutants were cultured as described with minor modifications (6,26). Briefly, frozen stocks of Mtb were revived in Middlebrooks's 7H9 media supplemented with ADC and subcultured thrice to logarithmic phase (A 595 , 0.3) by shaking (aerobic).…”
Section: Transcript Measurements From Mycobacteriamentioning
confidence: 99%
“…For the hypoxic setup, cultures (from above) were aliquoted in 2-ml cryovials (Sarstedt, Newton, NC) filled to the rim with bacteria, tightly sealed, wrapped with parafilm, and incubated at 37 8 C for 35 days (hypoxic). The bacteria were lysed, and RNA was purified as described (26).…”
Section: Transcript Measurements From Mycobacteriamentioning
confidence: 99%
“…A recent study has shown that sigma factors are required by some TCSs. The housekeeping sigma factor sigA participates in dormancy regulation by interacting with the TCS RR DevR [32]. DevR is a transcriptional regulator that activates the gene expression of dormant regulon and participates in the dormancy adaptation mechanisms of M. tuberculosis in response to hypoxia.…”
Section: Abstract: Drug Targets • Mycobacterium Tuberculosis • Pathogmentioning
confidence: 99%